2008
DOI: 10.1007/s10661-008-0692-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of trace metal pollution in surface sediments of Nemrut Bay, Aegean Sea

Abstract: Surface sediments collected from nine stations in Nemrut Bay, Aegean Sea were analyzed for trace metals (Hg, Cd, Pb, Cr, Cu, Zn, Mn, Ni, Fe, As, and Mg) and grain sizes. The results were compared with the numerical sediment guidelines used in North America as well as literature values reported for similar studies conducted in Izmit Bay and Izmir Bay. The metal levels were also evaluated according to the enrichment factor and contamination factor analyses. The analyses revealed significant anthropogenic polluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(42 citation statements)
references
References 32 publications
2
35
0
3
Order By: Relevance
“…In the study area, the Aliağa Bay sediment was found muddy except station 1which is located in the river flows. The Nemrut Bay, in station 5 and 6 were mainly muddy, station 7 and 8 contains mostly sand and these result showed similarities with Esen et al (2010). The higher total cyst abundance observed where the sediment contains mud and dinoflagellate cysts abundance changed depends on the sediment type for the Aliağa and Nemrut Bay.…”
Section: Discussionmentioning
confidence: 57%
“…In the study area, the Aliağa Bay sediment was found muddy except station 1which is located in the river flows. The Nemrut Bay, in station 5 and 6 were mainly muddy, station 7 and 8 contains mostly sand and these result showed similarities with Esen et al (2010). The higher total cyst abundance observed where the sediment contains mud and dinoflagellate cysts abundance changed depends on the sediment type for the Aliağa and Nemrut Bay.…”
Section: Discussionmentioning
confidence: 57%
“…The concentrations of elements in the Earth's crust are commonly chosen as the background values [18]. Fe was considered as the "conservative" element and has been commonly chosen as a reference element [19].…”
Section: Multivariate Analysis Methodsmentioning
confidence: 99%
“…Trace metals did not show strong seasonal variations. Gavriil and Angelidis (2005) The heavy metal content of the sediments in Nemrut Bay has been studied by Esen et al (2008). Contamination factors (CF) and Metal Enrichment Factors (EF) have been calculated.…”
Section: E Esenmentioning
confidence: 99%
“…Pb and As had very high contamination levels where there were considerable Zn contamination in most of the sediment samples [39]. Hg concentrations corresponded to very high contamination and the elevated enrichment levels of Pb (2.03-16.06) and Zn (1.08-8.52) indicated anthropogenic pollution (Esen et al, 2008). …”
Section: E Esenmentioning
confidence: 99%